2021
DOI: 10.3389/fcimb.2021.743390
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Fluoroquinolone-Resistant Escherichia coli in Healthy Children

Abstract: Faecal E. coli can act as reservoirs for resistance genes. Here, we analyzed prevalence of drug resistance in faecal E. coli isolated from healthy children at a single kindergarten in Beijing, China, then used whole genome sequencing to characterize fluoroquinolone-non-susceptible strains. Our results revealed high resistance to ampicillin (54.0%), trimethoprim/sulphurmethoxazole (47.5%) and tetracycline (58.9%) among 576 faecal E. coli isolates, 49.2% of which exhibited multidrug resistance. A total of 113 E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Several research groups have reported appreciable/considerable commensal carriage rates for ST131-H30 strains in healthy populations [ 2 , 3 , 4 , 5 , 15 , 16 , 17 , 18 ]. Interestingly both Zhao et al [ 16 ] and Cherubini et al [ 17 ] also detected colonization with ST1193 strains. In Zhao et al’s [ 16 ] study the ST1193 strains comprised the largest group of E. coli colonizing healthy children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have reported appreciable/considerable commensal carriage rates for ST131-H30 strains in healthy populations [ 2 , 3 , 4 , 5 , 15 , 16 , 17 , 18 ]. Interestingly both Zhao et al [ 16 ] and Cherubini et al [ 17 ] also detected colonization with ST1193 strains. In Zhao et al’s [ 16 ] study the ST1193 strains comprised the largest group of E. coli colonizing healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly both Zhao et al [ 16 ] and Cherubini et al [ 17 ] also detected colonization with ST1193 strains. In Zhao et al’s [ 16 ] study the ST1193 strains comprised the largest group of E. coli colonizing healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that E. coli are resistant to a number of antibiotics, including ampicillin, ampicillin/sulbactam, aztreonam, cefazolin, ceftazidime, ceftriaxone, cefepime, ciprofloxacin, gentamicin, moxifloxacin, nitrofurantoin, piperacillin/tazobactam, tobramycin, trimethoprim (Aabed et al, 2021). E. coli isolated from healthy children in China has extreme resistance to Ampicillin (54.0%), Arimethoprim/Sulphurmethoxazole (47.5%) and Tetracycline (58.9%) (Zhao et al, 2021). This research results showed that E. coli bacteria are resistant to a number of antibiotics, including ampicillin, ampicillin/sulbactam, aztreonam, cefazolin, ceftazidime, ceftriaxone, cefepime, ciprofloxacin, gentamicin, moxifloxacin, nitrofurantoin, beprazobactamide.…”
Section: Discussionmentioning
confidence: 76%
“…Mutations in the genes for DNA gyrase ( gyrA ) and topoisomerase IV ( parC ) are the main cause of resistance to these drugs, also known as the quinolone resistance-determining regions. Mutations in the genes gyrB and parE can also weaken the therapeutic effect of (fluoro) quinolones ( Hastak et al., 2020 ; Zhao et al., 2021 ). Target site mutation is a potential strategy for combating drug resistance.…”
Section: Antibiotic Resistance Of Several Prominent Toa Pathogensmentioning
confidence: 99%